1979
DOI: 10.1002/ana.410050111
|View full text |Cite
|
Sign up to set email alerts
|

Palatal myoclonus and denervation supersensitivity in the central nervous system

Abstract: We postulate that palatal myoclonus after infarction of the brainstem or cerebellum, or both, is the manifestation of denervation supersensitivity secondary to lesions involving the dentatorubroolivary system. Two cases of our own and 31 from the English and French literature were analyzed in order to determine the delay between the occurrence of presumed anatomical lesions and the recognition of palatal myoclonus. The intervals varied from 2 to 49 months with the median between 10 and 11 months. The natural h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…The spectrum of lesions varies from ischemic infarction, demyelination, and haemorrhage of various etiologies or trauma (3,5,6) . Pathologically hypertrophic olivary degeneration is characterized by cell body enlargement along with vacuolation of the cytoplasm, astrocytic hyperplasia and proliferation, demyelination and fibrillary gliosis are also seen.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of lesions varies from ischemic infarction, demyelination, and haemorrhage of various etiologies or trauma (3,5,6) . Pathologically hypertrophic olivary degeneration is characterized by cell body enlargement along with vacuolation of the cytoplasm, astrocytic hyperplasia and proliferation, demyelination and fibrillary gliosis are also seen.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be caused by a supra olivary lesion. Most theories propose an involvement of the pathways connecting the cerebellum to the inferior olivary nucleus [1][2][3]5,6 . Dubinski et al showed increased glucose metabolism in the medulla of 7 patients with PM 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of PM is variable, with better results in those with PPM [1][2][3]5,6,[10][11][12][13][14] . In all patients it should be carried a trial with sumatriptan, even those with possible secondary PM, to differentiate clinically the PPM from SPM 4,10,15 .…”
Section: Fig 2 Electromyography (Sumatriptan In the Case 1)mentioning
confidence: 99%
See 2 more Smart Citations